Clinical and subclinical mastitis in dairy cattle and buffaloes in Bihar, India: Prevalence, major pathogens and risk factors - Hardenberg, F. (Swedish University of Agricultural Sciences, 2016)
Bihar, located in north-eastern India, is a state with a growing dairy sector. Many people live under the poverty line and depend on the livestock and dairy production from cattle and buffaloes for their livelihood. Mastitis is known to result in substantial production and economic losses which can be crucial for small-scale dairy farmers. The knowledge about the situation regarding mastitis in Bihar is limited. The objectives of the study were to estimate the prevalence of mastitis in cattle and buffaloes, as well as to identify common udder pathogens and to identify possible risk factors of mastitis in cattle. The study was conducted in rural, peri-urban and urban households in Bihar during September and October 2015. In total, 285 cows and 28 buffaloes were included in the study. General information regarding herd and management factors was collected as well as details of the specific animals. The prevalence of subclinical and clinical mastitis was determined through clinical examination of the udder and by using California mastitis test (CMT) to evaluate somatic cell count in milk samples. Samples with CMT ≥3 were examined for presence of bacteria. Some of the samples were also tested with a rapid test (MastiTest) to evaluate sensitivity and resistance to antimicrobials. In cattle, the prevalence of subclinical and clinical mastitis was 35.4% and 11.6% respectively. The prevalence of subclinical mastitis in buffaloes was 28.6%, no cases of clinical mastitis were found. Out of 145 quarter milk samples from cattle, Staphylococcus aureus was the predominant bacteria (28.3%) followed by other Staphylococcus species (21.3%) and Streptococcus species (17.9%). Out of four quarter milk samples from buffaloes, three were negative for bacterial growth and one was contaminated. Floor type and presence of a drainage system had a significant association with prevalence of subclinical mastitis in cattle. Cows held on concrete floor had a lower prevalence of subclinical mastitis compared to cows kept on earthen or brick floor. Cows held in farms with a drainage system had a lower prevalence of subclinical mastitis. However, parity number, lactation stage and hygiene score had no association with the prevalence of mastitis in cattle. The results from the study indicate that the prevalence of mastitis in dairy cattle and buffaloes is high. Knowledge about preventive measures is essential to control mastitis. As for Bihar, preventive measures should be focused on emphasizing the importance of applying high hygienic standards of housing and milking practices.